Adolescent vaccine introductions scoping review: A decade of insights from low- and middle-income countries (2013−2023) - Arman Majidulla; Amelia K. Gerste; Anurima Baidya; Onimitein Georgewill; Kirthini K. Muralidharan; Degu J. Dare; Joeri S. Buis; Michelle M. Gill; Julie A. Denison; Andrew D. Kerkhoff; Rupali J. Limaye (Vaccine: X)
Background: Adolescents benefit from vaccines before infection – such as HPV – but parental consent and frequent social interactions complicate their introductions. We conducted a scoping review of the literature (2013 to 2023) on adolescent vaccine introduction efforts in low- and middle-income countries to examine lessons learned. Method: Following the PRISMA guideline, we searched four databases, screened abstracts and reviewed full text articles for inclusion. We included English full text articles which provided insights based on primary data collection into vaccine introductions for adolescents over the past ten years (i.e., 2013 onwards). We further searched the citations of included articles. We coded included articles for key characteristics and analyzed for thematic commonalities. Results: Twenty-six studies met our inclusion criteria, and the findings clustered across three distinct phases of new vaccine introduction: planning, implementation/delivery, and post-implementation/delivery. During the planning phase, the early engagement of stakeholders – particularly ministries of health and education - was critical for coordination and readiness. During implementation, school-based delivery was the most common approach, often supplemented by community outreach and mop-up activities to reach out-of-school adolescents. Opt-out consent was used as a strategy in some contexts in keeping with existing adolescent vaccine protocols. Vaccine rumors and conspiracy needed to be actively managed in some contexts. Post-introduction, health systems impacts were generally minimal and temporary, although human resource constraints and cold-chain gaps emerged in some settings. Several countries reported positive spillover effects, such as strengthened collaboration between health and education sectors, expanded adolescent health promotion, and investments in vaccine infrastructure. Conclusion: Adolescent vaccine introductions required multisectoral collaboration, flexible delivery models, and proactive community engagement. Future vaccine introductions would benefit from early stakeholder coordination and attention to context-specific delivery and consent strategies to ensure that vaccines are accepted, accessible, and equitably delivered.